Copeptin and NTproBNP in patients with acute Q - myocardial infarction complicated by acute heart failure with hyperglycemia on admission - Syvolap, Victor; Kapshytar, Nataliya (Journal of Education, Health and Sport, 2019)
Introduction. Acute heart failure is a complication of Q-myocardial infarction that affects the acute period and long-term outcome of the disease. The study of new predictors and outcomes of acute heart failure remains an urgent problem. Objective. To assess the levels of copeptin and NTproBNP in acute period of Q - myocardial infarction complicated by acute heart failure with hyperglycemia (HG) on admission. Materials and methods. The study involved 139 patients with acute MI Q-complicated by acute heart failure, who were divided into two groups: normoglycemia (n = 31) and HG on admission (n = 108). There were selected subgroups of HG: stress HG (n = 34), impaired glucose tolerance (IGT) (n = 26), new-onset type 2 diabetes (n = 25), type 2 diabetes mellitus (DM) in history (n = 23). The control group included 26 healthy individuals. The general clinical examination, echocardioscopy, continuous daily monitoring of ECG and blood pressure were performed, the levels of insulin, copeptin and NTproBNP were determined. Results. Compared with control group the patients with normoglycemia showed significantly higher level of copeptin on the first day by 27% (p = 0.03), in the group of HG on admission by 57% (p = 0.0001), in the stress HG group by 62% (p = 0.0001), in the group of new-onset diabetes by 49% (p = 0,001), in DM type 2 in history by 54% (p = 0,01). In patients with stress HG copeptin by 49% (p = 0.02), and in patients with GH on admission it was 2.3 times higher than in the normoglycemia group. On the 12thday the copeptin level was significantly higher than the values in the control group by 56% (p = 0.0009) in patients with normoglycemia, by 51% (p = 0,007) in group with the HG on admission, by 51% (p = 0.003) in stress HG patients. NTproBNP level was significantly higher that in the control on the first and 12th days in all groups. On the first day in patients with normoglycemia – 8,6 times (p = 0.00001), in group of HG on admission – 9,9 times (p = 0,00001), in stress HG patients – 11,2 times (p = 0.00001), in the group of IGT – 7,4 times (p = 0.0001), in patients with new-onset diabetes – 10,7 times (p = 0.00001), in the type 2 diabetes in history group – 12,2 times (p = 0.0001). On the 12th day NTproBNP level in patients with normoglycemia – 4.8 times (p = 0.001), in the group with HG on admission – 11.3 times (p = 0.00001), in stress HG – 11.1 times (p = 0.00001), in group of IGT – 12.8 times (p = 0.001), with new-onset diabetes – 7.14 times (p = 0.0002), in patients with DM type 2 in history – 11.7 times (p = 0.0001) higher than in the control group. In order to identify factors affecting the level of copeptin, a model of multiple linear regression was made. Conclusions. The most significant changes of copeptin were identified in groups of hyperglycemia on admission and stress HG. On the 12th day the increase of copeptin level, compared with the control group, retained in normoglycemia, hyperglycemia on admission and stress hyperglycemia patients. NTproBNP level was significantly increased in all patients, regardless of the presence and type of hyperglycemia. Systolic blood pressure in the pulmonary artery, the presence of the clinical manifestations of heart failure and hyperglycemia on admission have a predictive property, that allows to use them in the linear regression model to predict copeptin level.